Assessing the outcomes of prolonged cessation-induction and aid-to-cessation trials: floating prolonged abstinence. - Aveyard, P; Wang, D; Connock, M; Fry-Smith, A; Barton, P; Moore, D (2009)
INTRODUCTION: A Society for Research on Nicotine and Tobacco working group recommended outcome measures for cessation-induction trials and aid-to-cessation trials. Cessation-induction trials aim to motivate unwilling quitters to make a quit attempt. Aid-to-cessation trials give either medication or behavioral interventions to increase the rate at which willing quitters succeed in their attempts. Nicotine-assisted reduction programs combine features of both types of interventions by giving nicotine replacement to unwilling quitters. Treatment can be prolonged more than a year, quit attempts can occur and succeed early or late in the program, and renewed quit attempts are an inherent part of the program. Conventional outcome measures are tied to a fixed but arbitrary point in follow-up and cannot capture the true outcome: Prolonged cessation anchored to the point at which a person makes a successful quit attempt. DISCUSSION: We propose that the outcome should be counted from the successful quit attempt that began during the treatment period and continues for a defined period, ideally 6 months. In particular, if a trial compared a short reduction program with a long reduction program, it would not be possible to obtain an unbiased assessment of the outcome of such a trial using a measure tied to a fixed point in follow-up. Floating prolonged abstinence could provide such an assessment and is suitable for either prolonged cessation-induction trial or combined cessation-induction and aid-to-cessation trials.